Nanotherapeutics Using an HIV-1 Poly A and Transactivator of the HIV-1 LTR-(TAR-) Specific siRNA. (10th May 2011) - Mahajan, Supriya D.; Aalinkeel, Ravikumar; Reynolds, Jessica L.; Nair, Bindukumar; Sykes, Donald E.; Law, Wing-Cheung; Ding, Hong; Bergey, Earl J.; Prasad, Paras N.; Schwartz, Stanley A.
Abstract : HIV-1 replication can be efficiently inhibited by intracellular expression of an siRNA targeting the viral RNA. We used a well-validated siRNA (si510) which targets the poly A/TAR (transactivator of the HIV-1 LTR) site and suppresses viral replication. Nanotechnology holds much potential for impact in the field of HIV-1 therapeutics, and nanoparticles such as quantum rods (QRs) can be easily functionalized to incorporate siRNA forming stable nanoplexes that can be used for gene silencing. We evaluated the efficacy of the QR-si510 HIV-1 siRNA nanoplex in suppressing viral replication in the HIV-1-infected monocytic cell line THP-1 by measuring p24 antigen levels and gene expression levels of HIV-1 LTR. Our results suggest that the QR-si510 HIV-1 siRNA nanoplex is not only effective in delivering siRNA, but also in suppressing HIV-1 viral replication for a longer time period. HIV-1 nanotherapeutics can thus enhance systemic bioavailability and offer multifunctionality.